PillCam COLON 2© in Crohn's disease: A new concept of pan-enteric mucosal healing assessment - Carvalho, Pedro Boal (2015)
AIM To evaluate mucosal healing in patients with small bowel plus colonic Crohn's disease (CD) with a single non-invasive examination, by using PillCam COLON 2 (PCC2). METHODS Patients with non-stricturing nonpenetrating small bowel plus colonic CD in sustained corticosteroid-free remission were included. At diagnosis, patients had undergone ileocolonoscopy to identify active CD lesions, such as ulcers and erosions, and small bowel capsule endoscopy to assess the Lewis Score (LS). After = 1 year of follow-up, patients underwent entire gastrointestinal tract evaluation with PCC2. The primary endpoint was assessment of CD mucosal healing, defined as no active colonic CD lesions and LS < 135. RESULTS Twelve patients were included (7 male; mean age: 32 years), and mean follow-up was 38 mo. The majority of patients (83.3%) received immunosuppressive therapy. Three patients (25%) achieved mucosal healing in both the small bowel and the colon, while disease activity was limited to either the small bowel or the colon in 5 patients (42%). It was possible to observe the entire gastrointestinal tract in 10 of the 12 patients (83%) who underwent PCC2. CONCLUSION Only three patients in sustained corticosteroid-free clinical remission achieved mucosal healing in both the small bowel and the colon, highlighting the limitations of clinical assessment when stratifying disease activity, and the need for pan-enteric endoscopy to guide therapeutic modification.